INTRODUCTION AND MANAGEMENT OF PRIMATES ON ISLANDS IN THE PERUVIAN AMAZON - THOUGHTS ON A POTENTIAL PROBLEM - HEYMANN, Eckhard W. (2020)
This note discusses potential consequences of merging Isla Muyuy on the river Amazon which hosts an introduced (allochthonous) population of red-bellied tamarins, Saguinus labiatus (Callitrichidae), with the mainland, due to the Amazon’s riverine dynamics. It is recommended that an action plan be developed for this case, in order to avoid negative consequences for native populations of other species of tamarins and the ecosystem, in case Isla Muyuy joins the mainland.